2018
DOI: 10.31486/toj.18.0020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrieval vs Observation in Cylindrical Battery Ingestion

Abstract: Background: Battery ingestion, particularly in the pediatric population, has become more common since the development of button batteries. Consequently, formal recommendations regarding the management of this battery type have been developed. Larger cylindrical battery ingestion is less common, with fewer cases reported. As such, no clear practice guidelines have been developed for the management of cylindrical battery ingestion. Case Report: We present a case of an incarcerated adult who ingested 2 AA batteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…According to Hammami MB et al, for the patient who ingested two AA batteries, endoscopic removal was applied for the battery which was in the stomach, whereas for the one which passed to the duodenum a daily medical treatment with 17g polyethylene glycol 3350 pro-kinetic agent was applied and the patient ejected the second battery at the seventh day by defacation. 8 In our case, with no oesophageal obstruction, although he had laparotomy previously, we chose medical treatment method as the cylindrical AA battery remained in the stomach for less than 1 day.…”
Section: Discussionmentioning
confidence: 98%
“…According to Hammami MB et al, for the patient who ingested two AA batteries, endoscopic removal was applied for the battery which was in the stomach, whereas for the one which passed to the duodenum a daily medical treatment with 17g polyethylene glycol 3350 pro-kinetic agent was applied and the patient ejected the second battery at the seventh day by defacation. 8 In our case, with no oesophageal obstruction, although he had laparotomy previously, we chose medical treatment method as the cylindrical AA battery remained in the stomach for less than 1 day.…”
Section: Discussionmentioning
confidence: 98%
“…In other previous reports, a cylindrical battery that had moved beyond the pyloric ring into the small intestine was surgically removed, although, in recent years, most of the cases were followed up with the expectation of spontaneous elimination [5][6][7]. Hammami et al reviewed 15 cases and one case series of cylindrical battery ingestion and reported that no major complications occurred in asymptomatic cases at initial presentation, despite choosing conservative management [10]. Therefore, it is suggested that conservative management with close clinical monitoring might be possible if the patient is asymptomatic and the ingested battery cannot be seen by EGD.…”
Section: Discussionmentioning
confidence: 99%
“…Litovitz et al reported that of 8,648 cases of battery ingestion from 1990 to 2008 in the United States, 8,161 (94.4%) involved a button battery and 487 (5.6%) were cylindrical batteries [ 8 ]. Most cases of accidental ingestion of a button battery occur in children [ 9 ], whereas ingestion of a cylindrical battery is seen more commonly due to deliberate ingestion in a psychiatric population and by prisoners [ 10 ]. Our patient also had mental retardation as the underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…When ingested, cylindrical batteries can cause corrosive damage to the mucosal lining of the gastrointestinal tract (GIT), if their casing is damaged either by the acidic gastric content or deliberately prior to ingestion. If leakage occurs, patients will usually be symptomatic or have corrosive damage of the mucosa in endoscopy (Hammami et al , 2019). Furthermore, alkaline batteries contain metals including zinc, manganese, potassium hydroxide, mercury and an alkaline electrolyte solution that can cause liquefaction necrosis, erosions, ulceration and perforation, metal toxicity and hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%